Alu insertion polymorphisms in the African Sahel and the origin of Fulani pastoralists - Čížková, Martina; Hofmanová, Zuzana; Mokhtar, Mohammed G.; Janoušek, Václav; Diallo, Issa; Munclinger, Pavel; Černý, Viktor (Annals of human biology, 2017)
Background: The origin of Western African pastoralism, represented today by the Fulani nomads, has been a highly debated issue for the past decades, and has not yet been conclusively resolved. Aim: This study focused on Alu polymorphisms in sedentary and nomadic populations across the African Sahel to investigate patterns of diversity that can complement the existing results and contribute to resolving issues concerning the origin of West African pastoralism. Subjects and methods: A new dataset of 21 Alu biallelic markers covering a substantial part of the African Sahel has been analysed jointly with several published North African populations. Results: Interestingly, with regard to Alu variation, the relationship of Fulani pastoralists to North Africans is not as evident as was earlier revealed by studies of uniparental loci such as mtDNA and NRY. Alu insertions point rather to an affinity of Fulani pastoralists to Eastern Africans also leading a pastoral lifestyle. Conclusions: It is suggested that contemporary Fulani pastoralists might be descendants of an ancestral Eastern African population that, while crossing the Sahara in the Holocene, admixed slightly with a population of Eurasian (as evidenced by uniparental polymorphisms) ancestry. It seems that, in the Fulani pastoralists, Alu elements reflect more ancient genetic relationships than do uniparental genetic systems.